Realizing Efficient Single Organic Molecular White Light-Emitting Diodes from Conformational Isomerization of Quinazoline-Based Emitters - Li, Bowen; Li, Zhiyi; Guo, Fengyun; Song, Jinsheng; Jiang, Xi; Wang, Ying; Gao, Shiyong; Wang, Jinzhong; Pang, Xinchang; Zhao, Liancheng; Zhang, Yong (ACS applied materials & interfaces, 2020)
Single pure organic molecular white light emitters (SPOMWLEs) are of significance as a new class of material for white lighting applications; however, few of them are able to emit white electroluminescence from organic light-emitting diodes. Herein, donor−π–acceptor conjugated emitters, 2PQ–PTZ and 4PQ–PTZ, were designed and synthesized as SPOMWLEs for white light emission considering the distinct advantages of their conformation isomers. The coexistence of conformational isomers in 2PQ–PTZ, which is the first experimental evidence of the coexisting quasi-axial and quasi-equatorial conformers, provides ideal flexibility to obtain white light emission from their simultaneous and well-separated fluorescence and thermally activated delayed fluorescence. With these remarkable properties, a 2PQ–PTZ-based white light-emitting diode (LED) with a CIE of (0.32, 0.34) and color rendering index (CRI) of 89 is demonstrated. Further, the white organic light-emitting diode (OLED) of 2PQ–PTZ exhibits a high external quantum efficiency (EQE) of 10.1%, which is the reported highest performance among SPOMWLE-based OLEDs.